Determination of the best model to evaluate germination cardinal temperature of Silybum marianum as a medicinal plant - محمد علی دری; بهنام کامکار; مهناز اقدسی; الهه کمشی کمر (علوم و فناوری بذر ایران, 2014)
In order to evaluate cardinal temperatures of milk thistle (Silybum marianum)germination an experiment was carried out in the laboratory of Plant Production College, Gorgan University Agricultural Science and natural resources. Seven temperatures in a completelyrandomized design with four replications was used. Temperatures were 5 to 35ºC by 5ºC intervals. The seeds with 2 mm radicles were counted as germinated seeds.The germination rate percentage and cumulative seed germination percentage were calculated for each given temperatures.Cardinal temperatures (T-base, T-optimum and T-ceiling), also, were estimated using eight non linear regression models. The effect of temperature on total germination percentage, time to 50% germination (D50) and germination rate based on 1/D50 and mean germination time inverse (1/MGT) was significant at 1% of probability level. Results indicated that by increasing temperature up to 15ºC germination increased and after that declined. Based on the highest R² and the lowest MAE and RMSE segmented model was determined as the superior model. Thus, Tb, To and Tc for D50 (time to %50 germination) were estimated as 2.75, 31.51 and 38 using segmented model.To calculate germinationrate 1/D50 index was better than 1/MGT due to higher regression coefficient and less RMSE.